Diversity and Distribution of Traditional Home Gardens Along Different Disturbances in a Dry Tropical Region, India - Patel, Sanoj Kumar; Sharma, Anil; Singh, Rinku; Tiwari, Amit Kumar; Singh, Gopal Shankar (Frontiers in Forests and Global Change, 2022)
Home gardening is an indigenous practice of cultivation that has effectively adapted to local ecological conditions over generations. This study examined the effects of disturbance and garden size on the biodiversity of home gardens in order to develop a better understanding of vegetation cover and its role in livelihood provision in Vindhyan highlnads. Data was collected from 60 gardens which were classified into large (>650 m2), medium (400-650 m2) and small (<400 m2), on the basis of size and disturbance gradients viz., high, medium and low. A total of 133 species from 50 families were recorded, in which trees (47.4%) were dominating followed by shrubs (18%) and herbs (16.5%). Tree density were significantly (P ≤0.05) higher at LD (low disturbed) (293.75±16.1 individual ha-1) as compare to MD (medium disturbed) (221±11.5 individual ha-1) and HD (high disturbed) (210±10.3 individual ha-1). Species richness of tree was (P ≤0.05) highest at LD (7.40±.26) followed by HD (6.60±.17) and MD (6.20±21). However, the results for shrubs and herbs density were considerably different, where shrubs density were highest at HD (70±6.9 individual per 1000 m2) and lowest at LD (62.5±5.8 individual per 1000 m2), while maximum density of herbs were recorded at MD (466.25±29.8 individual per 100 m2) and minimum at LD (370±21.4 individual per 100 m2). Summed dominance ratio represented frequent use of garden plants in bio-fencing, vegetable, ornamental and ethno-medicine. Diversity (P<0.01) and species richness (P<0.05) show significant positive correlation with garden size. The Principal Component Analysis (PCA) showed that the first component (PC1) accounted for 28.6% variance, whereas second explained 21.9% variations in both disturbance and garden size with cumulative variance of 50.5%. These component depicted the positive association with HD (14.34), SDiv (13.91), TCD (12.47) and HDiv (12.09). We conclude that diversity of home gardens changes with disturbance, which may be an adaptive response towards the disturbance. This pattern highlights the importance of home gardens for local livelihood, which must be a viable option for the development of highly disturbed sites while also reducing the burden on dry tropical forest region.